Time‐dependent combinatory effects of active mechanical loading and passive topographical cues on cell orientation. Issue 10 (14th April 2016) - Wang, Qian; Huang, Hanyang; Wei, Kang; Zhao, Yi
ABSTRACT: Mechanical stretching and topographical cues are both effective mechanical stimulations for regulating cell morphology, orientation, and behaviors. The competition of these two mechanical stimulations remains largely underexplored. Previous studies have suggested that a small cyclic mechanical strain is not able to reorient cells that have been pre‐aligned by relatively large linear microstructures, but can reorient those pre‐aligned by small linear micro/nanostructures if the characteristic dimension of these structures is below a certain threshold. Likewise, for micro/nanostructures with a given characteristic dimension, the strain must exceed a certain magnitude to overrule the topographic cues. There are however no in‐depth investigations of such "thresholds" due to the lack of close examination of dynamic cell orientation during and shortly after the mechanical loading. In this study, the time‐dependent combinatory effects of active and passive mechanical stimulations on cell orientation are investigated by developing a micromechanical stimulator. The results show that the cells pre‐aligned by linear micro/nanostructures can be altered by cyclic in‐plane strain, regardless of the structure size. During the loading, the micro/nanostructures can resist the reorientation effects by cyclic in‐plane strain while the resistive capability (measured by the mean orientation angle change and the reorientation speed) increases with the increasing characteristic dimension. The micro/nanostructures also can recover the cell orientation after the cessation of cyclic in‐plane strain, while the recovering capability increases with the characteristic dimension. The previously observed thresholds are largely dependent on the observation time points. In order to accurately evaluate the combinatory effects of the two mechanical stimulations, observations during the active loading with a short time interval or endpoint observations shortly after the loading are preferred. This study provides a microengineering solution to investigate the time‐dependent combinatory effects of the active and passive mechanical stimulations and is expected to enhance our understanding of cell responses to complex mechanical environments. Biotechnol. Bioeng. 2016;113: 2191–2201. © 2016 Wiley Periodicals, Inc. Abstract : The combinatory effect of active (cyclic strain) and passive (linear surface wrinkles) mechanical stimulations on cell orientation was investigated. The results demonstrate that cyclic strain can reorient cells regardless of wrinkle size, while the reorienting behavior varies with strain magnitude and wrinkle size. Surface wrinkles can reorient the cells after strain removal, while the reorientation capability likewise varies with wrinkle size. The observation time point is thus critical for accurate interpretation of cell behavior under the combinatory mechanical stimulations.